The Milan System for Reporting Salivary Gland Cytopathology: A 3-year Retrospective Analysis in Patan Hospital - Gautam, Dipti; Thapa, Rojin (Nepalese Medical Journal, 2022)
Introduction: The characteristics of salivary gland lesions identified by fine-needle aspiration cytology are varied and may overlap, which makes diagnosis difficult for cytopathologists. To provide consistency in the reporting of salivary gland cytology and to enhance clinic-pathologic communication, the "Milan system for reporting salivary gland cytopathology" has been introduced, which offers guidelines for diagnosis and treatment based on various categories of malignancy risk. Material and Methods: In this retrospective study, Fine needle aspiration cytology was done for all salivary gland lesions for three years and were retrieved from the Department of pathology, Patan hospital. All the cases were recategorized according to the Milan system for reporting salivary gland cytology with histopathology follow-up wherever available. Consistency of the two different types of assessment techniques (Milan category and primary cytology diagnosis) were assessed and the k score was calculated Results: A total of 58 cases were included in the study of which histological follow-up was available in 27 cases. Out of 58 cases, maximum cases 32 (55.1%) were classified under IVA followed by 15.5% cases classified under II, 8.6% of cases under Category IVB), 6.8% under category Vand 5.1% cases under category VI. Kappa's score was 0.58 which represents a moderate agreement. Conclusions: Milan system for reporting salivary gland cytopathology is a recently proposed six-category scheme, which places salivary gland fine needle aspiration cytology into well-defined categories that limit the possibilities of false negative and false positive cases.